Scale‐dependent effects of nonnative plant invasion on host‐seeking tick abundance. Issue 3 (25th March 2016) - Adalsteinsson, Solny A.; D'Amico, Vincent; Shriver, W. Gregory; Brisson, Dustin; Buler, Jeffrey J.
Abstract: Nonnative, invasive shrubs can affect human disease risk through direct and indirect effects on vector populations. Multiflora rose ( Rosa multiflora ) is a common invader within eastern deciduous forests where tick‐borne disease (e.g., Lyme disease) rates are high. We tested whether R. multiflora invasion affects blacklegged tick ( Ixodes scapularis ) abundance and at what scale. We sampled host‐seeking ticks at two spatial scales: fine scale, within R. multiflora ‐invaded forest fragments; and patch scale, among R. multiflora ‐invaded and R. multiflora ‐free forest fragments. At a fine scale, we trapped 2.3 times more ticks under R. multiflora compared with paired traps 25 m away from R. multiflora . At the patch scale, we trapped 3.2 times as many ticks in R. multiflora ‐free forests compared with R. multiflora ‐invaded forests. Thus, ticks are concentrated beneath R. multiflora within invaded forests, but uninvaded forests support significantly more ticks. Among all covariates tested, leaf litter volume was the best predictor of tick abundance; at the patch scale, R. multiflora ‐invaded forests had less leaf litter than uninvaded forests. We suggest that leaf litter availability at the patch scale plays a greater role in constraining tick abundance than the fine‐scale, positive effect of invasive shrubs.